Advances in library administration and organization. Vol. 26 - Garten, Edward D. (Emerald, 2008)
This collection of essays is designed to challenge working administrators and researchers to look more closely at their operations and consider again how they develop people and the organizations in which they work. It leads off with an article on skill development in reference service using a holistic approach to analyze reference in context. Then comes an article on the importance of organizational culture in defining service organizations in general and libraries in particular. It argues that when one considers libraries in this light, the importance of a strong ethical framework becomes evident in our institutions. The third article looks at advice networks, and addresses the importance that contacts within and outside of the library in which we work and within and outside of our profession play on individual's receptivity to innovation.The next three articles relate to personnel matters. The first discusses issues relating to the relationship between faculty status and tenure and salaries in academic libraries. This is followed by a piece that looks at the development of leaders for small, rural libraries, most of whom will not have formal training in librarianship. A third piece analyzes the criteria for selecting academic library directors that are considered important by those administrators who oversee this key leadership position.We then close with an article that looks at the validity of SERVQUAL as applied to a large public library system. LibQUAL+, an adaptation of SERVQUAL designed for use in academic libraries has become a staple in our literature for years, but there is little available that really turns a critical eye to the use of this important tool. This article will perhaps begin a healthy discussion about how this tool is applied in our libraries and how the results have been used in library operations.As always, this volume of Advances attempts to look at what it is we do as managers and to bring research and theory into our operations. It is designed to combine the practical and the theoretical in a way that will inform working managers and provide interesting questions for those engaged in research about library organizations.
Includes indexes.
Keywords: Language Arts & Disciplines -- Library & Information Science -- General.; Library, archive & information management.; Library administration.; elektronické knihy; electronic books